Ethylene Perception by the ERS1 Protein in Arabidopsis - Hall, Anne E. (American Society of Plant Physiologists, 2000)
Ethylene perception in Arabidopsis is controlled by a family of five genes, including ETR1, ERS1 (ethylene response sensor 1), ERS2, ETR2, and EIN4. ERS1, the most highly conserved gene with ETR1, encodes a protein with 67% identity to ETR1. To clarify the role of ERS1 in ethylene sensing, we biochemically characterized the ERS1 protein by heterologous expression in yeast. ERS1, like ETR1, forms a membrane-associated, disulfide-linked dimer. In addition, yeast expressing the ERS1 protein contains ethylene-binding sites, indicating ERS1 is also an ethylene-binding protein. This finding supports previous genetic evidence that isoforms of ETR1 also function in plants as ethylene receptors. Further, we used the ethylene antagonist 1-methylcyclopropene (1-MCP) to characterize the ethylene-binding sites of ERS1 and ETR1. We found 1-MCP to be both a potent inhibitor of the ethylene-induced seedling triple response, as well as ethylene binding by yeast expressing ETR1 and ERS1. Yeast expressing ETR1 and ERS1 showed nearly identical sensitivity to 1-MCP, suggesting that the ethylene-binding sites of ETR1 and ERS1 have similar affinities for ethylene.